Improving Oral Language Skills Through Storytelling in Group B of Dasa Wisma Ketong Kindergarten - Dina Purnamasari; Nurhayati Nurhayati; Armina Muthar; Andi Agusniatih (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
Early childhood education contributes significantly to building the foundation of children's development, including language, which is the foundation of communication, early literacy, and social-emotional skills. However, observations show that most children aged 5–6 years still experience difficulties in oral language, such as difficulty telling stories, difficulty answering questions, and limited vocabulary. The purpose of this study was to improve children's oral language skills through the application of interactive storytelling methods. The study used the Classroom Action Research (CAR) design model of Kemmis & Mc Taggart, which was implemented in two cycles on 10 children in Group B of Kindergarten. Data collection was carried out through observation, performance assessment, interviews, and documentation, then analyzed qualitatively with triangulation of techniques and sources. The results showed an increase in oral language skills in three main aspects, namely fluency, accuracy, and vocabulary. In the first cycle, the majority of children were in the "Beginning to Develop" and "Developing as Expected" categories, while in the second cycle there was a significant increase with most children reaching the "Developing Very Well" category. The application of interactive storytelling with a variety of media, teacher reflection, and active child involvement has proven successful in creating more interactive and meaningful learning. This study concludes that storytelling is an effective strategy for stimulating early childhood oral language skills while strengthening self-confidence, creativity, and social interaction. The practical contribution of this research is that it provides a reflective storytelling model that early childhood education teachers can adapt in their daily learning.